Clinical characteristics of headaches in an urban Mennonite group in South Brazil - Dück, David Lemke; Utiumi, Marco Antonio Takashi; Boldt, Angelica Beate Winter; Piovesan, Elcio Juliato (Arquivos de Neuro-Psiquiatria, 2023)
Background Genetic variants play a pathophysiological role in headaches, especially in migraine. The Mennonite group (MG) has been geographically and genetically isolated throughout its history, harboring a distinctive distribution of diseases.Objective To determine the characteristics of headaches in a group with direct Mennonite ancestry contrasting with other urban community members (control group [CG]).Methods Subjects with headaches were asked to complete a questionnaire covering: the type of headache, presence of aura, frequency and duration of attacks, pain location and severity, analgesic consumption, premonitory and postdromic manifestations, Depressive Thoughts Scale, Epworth Sleepiness Scale (ESS), General Anxiety Disorder-7, Patient Health Questionnaire-9 (PHQ-9), Migraine Disability Assessment, and Composite Autonomic System Score.Results We included 103 participants (CG: 45, Mennonite group [MG]: 58). Migraine was the most common headache (CG: 91.1%; MG: 81.0%; p = 0.172), followed by tension-type headache (CG: 8.9%; MG: 15.5%; p = 0.381). Aura was identified by 44.4% and 39.7% in the CG and MG, respectively (p = 0.689). The groups differed only concerning the frequency of retro-orbital pain (CG: 55.6%; MG: 32.8%; p = 0.027), PHQ-9 (CG: median 7, range 0 to 22; MG: median 5, range 0 to 19; p = 0.031) and ESS (CG: median 0, range 0 to 270; MG: median 0, range 0 to 108; p = 0.048) scores.Conclusion There were no major differences in the prevalence and clinical characterization of headaches between the MG and the CG. However, the latter showed more diffuse pain, sleepiness, and depressive symptoms. Specific genetic or epigenetic variants in Mennonite descendants might account for these differences.
Keywords: Reproductive Isolation; Migraine Disorders; Urban Population; Headache